The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.30935/cedtech/6107
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scale to Explore Technology Literacy Skills of Turkish 8th Graders

Abstract: The use of emerging technologies shape learners' knowledge creation and transformation processes. In this regard, this study aimed to develop a scale to investigate 8 th graders' competencies regarding the educational technology standards based on ISTE-NETS. After a review of relevant literature, an item pool was prepared. The pool was improved through expert opinions and pilot implementations. The items were administered to 620 Turkish students from six different cities for the exploratory factor analysis (EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This self-reported CTS can be easily used for surveys with large samples to quickly gain the profiles of the computational thinking competencies for all students at all school levels. Finally, relationships between students' computational thinking competencies and traditional computer literacy competencies (Misirli & Akbulut, 2013), such as online information searching and evaluation competencies (Tsai, 2009a) and online discussion competencies (Tsai, et al, 2015), can be further examined using the CTS instrument developed in this study. All the above research results may provide valuable information and suggestions for educational policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…This self-reported CTS can be easily used for surveys with large samples to quickly gain the profiles of the computational thinking competencies for all students at all school levels. Finally, relationships between students' computational thinking competencies and traditional computer literacy competencies (Misirli & Akbulut, 2013), such as online information searching and evaluation competencies (Tsai, 2009a) and online discussion competencies (Tsai, et al, 2015), can be further examined using the CTS instrument developed in this study. All the above research results may provide valuable information and suggestions for educational policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…After specifying their problems, I supposed that their problems might have been caused because of inadequate digital literacy skills. I decided to measure their digital literacy skills by using a questionnaire developed by Misirli and Akbulut (2013). This questionnaire was created to explore the learners' digital literacy skills.…”
Section: Methodsmentioning
confidence: 99%
“…It is emphasized that the researcher should recruit at least five people per item when carrying out factor analysis (24). In the literature, it has been reported that a sampling size less than 100 is considered as insufficient for developing a scale, 100-200 as medium, 200-300 as good, 300-500 as very good, and 500-1.000 as excellent (25,26). This study was conducted with 3 rd year students taking a pediatric nursing course and 4 th year students carrying out their internship training in the field of pediatric nursing in the spring semester of the 2017-2018 academic year at the Nursing Faculty of a state university.…”
Section: Study Design Sampling and The Populationmentioning
confidence: 99%